Comparison between nitriding behavior of Mo-Ti and Mo-V alloys. (April 2023) - Akhlaghi, Maryam; Körner, Carolin
Abstract: Internal nitriding behavior of Mo-15 at.% Ti and Mo- 5/15 at.% V alloys were compared in a temperature range from 700 °C to 1100 °C using Forming gas (95% N2 and 5% H2 ) for nitriding times of 10 h and 15 h. The variations of specimen weight, microstructure and hardness of nitrided layer as well as the developed nitriding products were investigated as a function of treatment temperature and time. VN and TiN nitrides with a minor amount of TiO2 oxide are formed on the surface of Mo-V and Mo-Ti alloys, respectively. The maximum nitrided depths of around 14 μm are achieved for both Mo-15 Ti/V alloys after nitriding at 1100 °C for 10 h. Larger hardness values are measured on nitrided layer of Mo-Ti in comparison to that of Mo-V at the same treatment temperature. According to X-ray diffraction assessment, at moderate temperature of 900 °C, the diffraction of Mo matrix and VN nitrides is recognized as an incoherent diffraction, whereas coherent diffraction by matrix and nitrides is realized for Mo and TiN. In general, higher affinity of nitride formation for V is observed at lower temperature of 700 °C as compared to Ti in a Mo matrix, which is attributed to the stronger interaction of V and N in Mo matrix given by calculating corresponding interaction parameters. The difference in stress relieving and coarsening behavior were also observed in matrices containing VN and TiN, which is argued with regards to the dissimilar impacts of VN and TiN on precipitation hardening of Mo matrix at investigated temperatures. These results imply that the previously reported brittleness of Mo-based alloys containing Ti can be improved at moderate temperatures by replacing Ti with other nitride forming elements such as V, regardless of N concertation in Mo matrix. Highlights: Internal nitriding behavior of Mo-15 Ti and Mo-15 V alloys were compared between 700 and 1100 °C. Larger hardness values are measured on nitrided layer of Mo-Ti as compared to that of Mo-V. Higher affinity for nitride formation is observed for V as compared to Ti in a Mo matrix. Differences in stress relieving and coarsening behavior are realized in Mo-matrices containing VN and TiN.